Self-assembly of pyrene-appended glucono gelators: spacer regulated morphological change and inversion of circularly polarized luminescence. Issue 12 (13th February 2020) - Liu, Zongwen; Jiang, Yuqian; Jiang, Jian; Yuan, Chenhuan; Wang, Decai; Liu, Minghua
Abstract : Pyrene-appended glucono gelators with different spacer lengths (two and four methylene units) were designed and found to form supramolecular gels in organic aqueous solvents. Abstract : Pyrene-appended glucono gelators with different spacer lengths (two and four methylene units) were designed and found to form supramolecular gels in organic aqueous solvents. The shorter spacer gelator 1 was prone to self-assemble into nanotubes due to well stacking multi-bilayer unit, while gelator 2 with the longer spacer formed nanofibers due to the relatively disordered packing structure. Both of the gels showed supramolecular chirality as well as circularly polarized luminescence (CPL) due to the chirality transfer from the glucose moiety to the assembly. Interestingly, the CD and CPL signals were opposite for the two gels. It was suggested that the packing of the pyrene unit in the gels were different due to the spacer and resulted in the inversed chiroptical properties. The work provided a deeper understanding of the origin of the supramolecular chirality and furthers the design of the CPL materials.